The Use of Big Book Media to Improve Students' Conceptual Understanding Abilities in Islamic Education Learning at SMPIT Darul Muta'allimin - Evida; Mizasari, Ana (Jurnal Profesi Guru Indonesia, 2025)
This research aims to improve students' ability to understand concepts in Islamic Religious Education (PAI) learning through the use of big book media at SMPIT Darul Muta'allimin. The method used is Classroom Action Research (PTK) which is carried out in two cycles with the research subject of grade VIII students. Data collection instruments include observation, concept comprehension tests, and documentation. The results of the study showed a significant increase in students' ability to understand concepts. In the initial condition, only 50% of students achieved the Minimum Completeness Criteria (KKM) with an average score of 65. After the implementation of big book media in the first cycle, the percentage of students who completed increased to 70% with an average score of 72, and in the second cycle it reached 85% with an average score of 80. This increase indicates that the use of big book media is effective in improving students' understanding of concepts in PAI learning. Big book media provides visual stimulus that strengthens students' memory and understanding of the subject matter, while increasing students' interest in learning. In conclusion, big book media can be used as an alternative learning media to improve the quality of PAI learning at SMPIT Darul Muta'allimin.